Earlier Radiosurgery Leads to Better Pain Relief and Less Medication Usage for Trigeminal Neuralgia Patients: An International, Multi-center Study. (1st September 2019) - Mureb, Monica; Golub, Danielle; Benjamin, Carolina Gesteira; Strickland, Ben A; Zada, Gabriel; Chang, Eric L; Warnick, Ronald E; Speckter, Herwin; Eastman, Skyler; Kaufmann, Anthony M; Feliciano, Caleb E
Abstract: INTRODUCTION: Trigeminal neuralgia (TN) is a chronic pain condition that is difficult to control with one or more medications. Disabling medication-related side effects are common, and benefit typically wanes over time. This study examined how stereotactic radiosurgery (SRS) affects outcomes and medication usage based on the time course between diagnosis and radiosurgery. METHODS: We conducted a retrospective review of patients with Type I TN at 11 Gamma Knife treatment centers. SRS was the primary surgical intervention in all patients. Patient demographics, disease characteristics, treatment plans, medication histories, and outcomes were documented. Univariate and multivariate statistical analyses were used where appropriate; multivariate regressions were based on contributing variables where P  < .3 in univariate analysis with covariates maintained if a significance level of P  < .05 was achieved. RESULTS: A total of 286 patients were included. Average follow-up was 27.4 mo. Patients who received SRS within 4 yr of initial diagnosis demonstrated a significantly shorter time to pain relief than those who received SRS later (median 21 d vs 27 d, P  = .030*). SRS significantly reduced the number of medications used both overall (mean 1.92 vs 0.96, P  ≤ .0001*) and in each medication class by last follow-up. In multivariate analysis, higher maximum radiation dose was a robust predictor of durable pain response (OR 1.13, P  = .001*) and, correspondingly, a negative predictor of treatment failure (OR 0.87, P  = .0005*). Overall adverse radiation effect rate was low (2.45%) and not associated with maximum dose. CONCLUSION: Patients managed with SRS within 4 yr of diagnosis experienced a shorter interval to pain relief with low risk. SRS yielded significant decreases in adjunct medication utilization. Radiosurgery should be considered earlier in the course of patient care for TN.